The elusive Sobralia amabilis (Orchidacae): a range extension of its distribution to Alta Verapaz, Guatemala, with notes on its habitat - Grajeda–Estrada, Rafael; Rustrián–López, Juan Pablo; Serrano, Marcelo José; Villalobos–Soberanis, Andrés; Maldonado, Mayra L.; Álvarez–Ruano, María Renée; Dix, Margaret A. (Lankesteriana: International Journal on Orchidology, 2020)
We present a range extension for Sobralia amabilis, previously recorded from the southeastern border of Guatemala to Panama and Ecuador. Here, we detail its taxonomic history, description, and geographical distribution, along with photographs of the plants in vivo, habitat notes and recommendations for collecting and preparing herbarium specimens.